2013
DOI: 10.1186/1756-0500-6-473
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drug utilization in Bangladesh: experience from Dhaka Medical College Hospital

Abstract: BackgroundEpilepsy is a common health problem which carries a huge medical social psychological and economic impact for a developing country. The aim of this hospital-based study was to get an insight into the effectiveness and tolerability of low cost antiepileptic drugs (AEDs) in Bangladeshi people with epilepsy.MethodsThis retrospective chart review was done from hospital records in weekly Epilepsy outdoor clinic of Department of Neurology, Dhaka Medical College Hospital (DMCH) from October 1998 to February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
5
14
2
Order By: Relevance
“…GTCS was found to be the commonest seizure type encountered, which is in line with studies conducted in Saudi Arabia (65%) [20] and Bangladesh (74%) [21]. Choice of the most appropriate AEDs depends on proper classification of seizures type.…”
Section: Discussionsupporting
confidence: 81%
“…GTCS was found to be the commonest seizure type encountered, which is in line with studies conducted in Saudi Arabia (65%) [20] and Bangladesh (74%) [21]. Choice of the most appropriate AEDs depends on proper classification of seizures type.…”
Section: Discussionsupporting
confidence: 81%
“…20 In contrast, in a study conducted by Mathur S et al phenytoin was responsible for most of the ADRs. 6 Also, the studies of Sebastian J et al 7 Jena M et al 18 and Habib M et al 21 showed that phenytoin was responsible for 53.3%, 51.6% and 64%, of the ADRs, respectively. The increase in the numbers of ADRs due to phenytoin in the previous studies is possibly due to the prescribing patterns of AED in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…this higher predominance could be due to the high incidence of sodium valproate used by patients in the present study. While GI disturbances were most common ADR reported in the study of Sebastian J et al 7 Whereas gum hyperplasia was mostly experienced by the patients enrolled in the study of Habib M et al 21 In the study of Hansens Y et al…”
Section: Acknowledgementmentioning
confidence: 98%
“…Antiepileptic DUS in a Bangladesh medical college hospital in 2013concludes that the use of older AED's like valproate, CBZ, phenytoin, and phenobarbitone is a very cost-effective therapy in primary healthcare settings [29]. Valproate was also the only drug supplied free of cost during the study period in RMMCH pharmacy and this also could have been a reason for its wide use in prescriptions for seizures, as it mainly contributes in increasing the compliance of patients.…”
Section: Resultsmentioning
confidence: 99%